The Effect of Secretome on Post-Laparotomy Wound Healing in Female Wistar Rats - Haris Nur Ashfi Arifa; Heru Priyanto; Abdurahman Laqief; Adrianes Bachnas; Hermawan Udiyanto (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2026)
Background: Secretome is defined as a set of bioactive molecules produced by cells in the extracellular space, which include but are not limited to proteins, nucleic acids, proteasomes, exosomes, microRNAs, and membrane vesicles. Secretome has received considerable attention in wound care, both in vitro and in vivo studies have demonstrated the ability of secretome to aid the wound healing process by accelerating angiogenesis, reducing inflammation, and stimulating fibroblast and keratinocyte proliferation.Objective: This study aims to determine the effect of administering secretome on post-laparotomy wound healing in female Wistar rats.Methods: A post-test control group design laboratory experimental study compared the REEDA scale and modified VSS score as indicators of post-laparotomy wound healing process in female Wistar rats. A sample of 30 rats was divided into three treatment groups. Group A was the control group that was not given injection, group B was given phosphate buffer saline (PBS) injection, and group C was given subcutaneous injection of UCMSC secretome. The injection treatment was carried out on the 3rd day post-laparotomy according to the wound healing phase. The development of the wound healing process was documented and observed through REEDA scale assessment on days 6, 9, 12, 15, 18, and 21 of the study and scar tissue was carried out on the 21st day of the study using the modified VSS score.Results: The Kruskal Wallis test showed significant results on the REEDA scale on day 6 (p = <0.01), day 9 (p = 0.002), day 12 (p = <0.01), and day 15 (p = 0.008). Significant Post Hoc tests on days 6, 9, 12, and 15 showed that the UCMSC secretome had the most effect on reducing the REEDA scale. On the VSS score, the Kruskall Wallis test showed significant results (p = 0.005). Post Hoc tests on the modified VSS score showed that the UCMSC secretome had the most significant effect on the modified VSS score.Conclusion: UCMSC secretome has a decreasing effect on the REEDA scale and Modified VSS score on the post-laparotomy wound healing process in female Wistar rats so that it can be considered as a therapeutic option for post-laparotomy wound healing.